KEBEBASAN BERSUARA DARI PERSPEKTIF SIASAH SYAR’IYAH - Abdul Rahman, Mohamad Zaidi (Jurnal Syariah, 2019)
This article attempts to evaluate the position of speech's freedom from the perspective of Siyasah Syar'iyyah. It is observed that this right falls under the obligatory category particularly in order to achieve the purpose of the establishment of Islamic state based on the Quran dan the Sunnah.